“Islamic State” and the North Caucasus in the Middle East Perspective: Challenges to and Lessons for Russia - A. Yarlykapov (Международная аналитика, 2016)
The author considers, in the broad Middle East perspective, the impact of the ISIS and its activities on the situation in the North Caucasus. An analysis is suggested of the recent trends in Russian Islamic community and in the whole Ummah as well as challenges to Russia from the ISIS. The article also proposes some recommendations aimed to reduce security threats to our country.